Circadian time-keeping system in birds: A review - Mishra, Ila (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2017)
In contrast to the highly centralised circadian clock in mammals, where the master clock resides in the anterior hypothalamic nucleus, as suprachiasmatic nucleus (SCN), the avian circadian timing machinery is more complicated with 3 circadian clock centres- the retina, hypothalamus and pineal. These three autonomous circadian oscillators interact with one another to regulate overt circadian rhythms in birds. Further, the contribution of each of these pacemakers is very diverse among different species. The homologue of mammalian SCN in birds is differentiated in two nuclei: medial SCN (mSCN) and the visual SCN (vSCN). Both mSCN and vSCN communicate through bidirectional and bilateral projections; allow them to communicate the light information with each other. Further, retinal photoreception via retinohypothalamic tract (RHT) is not the only photic input projected to the circadian clock machinery in birds. Many studies suggest that in birds, the entrainment of the endogenous circadian system by 24-hour light –dark (LD) cycles can persist even after enucleation. Circadian pacemaker in the pineal and in eyes of some avian species talks with the hypothalamic pacemaker via rhythmic synthesis and release of the melatonin hormone. In most of avian species, arhythmicity occurs following pinealectomy. Thus the disruption of circadian timing induced by pinealectomy support the hypothesis that the pineal is the locus of a major circadian pacemaker that controls the period and phase of other circadian oscillators and, in the absence of this pacemaker, the rest of the system is unable to maintain coherent circadian organization.